A Next Generation Wholesaler’s View of the NBN - How Retail Service Providers can succeed in an NBN world - Branson, Sarah; Sugo, Rene (Journal of Telecommunications and the Digital Economy, 2016)
The MNF Group has been operating in the Australian Telecommunications market since 2004. The author of this paper is an employee of the MNF Group and the opinions expressed are those of the author and do not necessarily represent those of the MNF Group. Upgrading the infrastructure of an entire country is a huge undertaking and was deemed necessary with Government intervention in Australia. Had this task been left to private companies, the likelihood is that Australia would continue to experience a huge gap between the cost and availability of high quality, fast speed broadband services between metro and rural regions. The NBN rollout is several years into the project and a recently released report from the ACCC has given insights into the wholesale market and initial market indicators shows that the market is becoming less competitive. This paper examines the costs of interconnecting with the NBN and demonstrates why the NBN has not achieved its goal of providing a level playing field for all telecommunication companies. By looking at the true cost of providing NBN services to NBN users, it is shown that the NBN pricing model is flawed and will affect the quality of service being provided to Australians. To succeed in the telecommunications industry, it is suggested that smaller RSPs will need to work hard to differentiate their brand and provide added value to consumers through additional service offerings. Selling NBN services alone will not be enough to enable smaller RSPs to survive in this tough market. It can be expected that there will be further RSP consolidation within the telecommunications industry as the smaller RSPs won’t be able to compete with the big 4 dominating the market.